2013
DOI: 10.12968/denn.2013.9.8.464
|View full text |Cite
|
Sign up to set email alerts
|

Cystic fibrosis in paediatric dental patients

Abstract: Cystic fibrosis is a common genetic disorder and presents challenges to the dental team. This article reviews the necessary considerations for the successful management of paediatric dental patients with cystic fibrosis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…After comparing children with CF with healthy children, studies agree that there was little difference in the primary dentition [14], with statistical significance mostly in the permanent teeth [7], more frequently in the permanent first molars and maxillary central incisors [6]. Teeth that are formed during the embryonic period are less exposed to deterioration factors [3];…”
Section: Prevalence Of Dental Hard Tissue Defects In Patients With Cfmentioning
confidence: 99%
See 4 more Smart Citations
“…After comparing children with CF with healthy children, studies agree that there was little difference in the primary dentition [14], with statistical significance mostly in the permanent teeth [7], more frequently in the permanent first molars and maxillary central incisors [6]. Teeth that are formed during the embryonic period are less exposed to deterioration factors [3];…”
Section: Prevalence Of Dental Hard Tissue Defects In Patients With Cfmentioning
confidence: 99%
“…It has been shown that cystic fibrosis may be associated with delayed tooth eruption [14]. It is thought that dental germ development, because of its high sensitivity to systemic disturbances (CFTR dysfunction, systemic conditions, medications used), often acts as a biomarker of systemic involvement [3].…”
Section: Etiologies Of Enamel Defectsmentioning
confidence: 99%
See 3 more Smart Citations